(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Community policing is the collaboration between the police and the general public or community which detects the problems in the society and solves those problems and also, it’s a joint vigilance on forthcoming anti-social elements in the society. The use of unnecessary force and arrogance, aloofness, or rudeness at any level of the agency will reduce the willingness of community members to ally themselves with the police. The effective mobilization of community support requires different approaches in different communities. It’s essential to address societal perceptions and stereotypes that may discourage women from considering a career in law enforcement. Education and awareness campaigns should be launched to challenge these stereotypes and showcase the diverse roles and opportunities available within the police force. Community Policing is being an very effective instrument in controlling crime in the modern society. Many of the developing countries like India and other developed countries are adopting Community Policing system, not only adopting and practicing, but in some places Community Policing is taken over and replaced the regular traditional policing system.